MSMEs Financial Sustainability Model in Indonesia: Policy, Capital, Literacy, Structure - Heliani Heliani; Yusuf Iskandar (Universitas Muhammadiyah Malang, 2024)
Purpose: This study looks into the intricate relationships that exist between capital structure, financial literacy, intellectual capital, social capital, and government policies in relation to the sustainability and financial performance of MSMEs in Indonesia. Methodology/approach: This study used structural equation modeling (SEM-PLS) for quantitative analysis with a sample of 375 firms. Findings: The findings support the significance of these elements and highlight complex connections that add to a comprehensive knowledge of MSMEs dynamics. Notably, the effects of government policies on sustainability financial and performance are varied. Practical implications: For academics, practitioners, and policymakers seeking to support MSMEs growth and resilience in the particular Indonesian setting, these findings provide practical insights. Originality/value: In doing so, the study aims to elucidate the complex interrelationships among these variables and their collective impact on the operational efficiency and long-term viability of MSMEs in Indonesia.